Digital Algorithmic Generative Method of Case-based Design The generation of Primary School Plans as a Case Study (Journal of University of Babylon for Engineering Sciences, 2020)
The use of programming languages in the field of architecture has strengthened the digital algorithmic approaches in the architectural design, which their main benefits lie in the possibility of rapid and easy generation of a wide range of design solutions. The generation and evaluation of more design solutions lead to more informed design decisions and the selection of the appropriate solution.The research adopted the digital algorithmic approach to generating architectural plans and investigates the possibility of using the visual programming applied in Grasshopper, the (plug-in) of Rhinoceros software. Its aim was to create and implement an algorithm prepared by researchers, which depends on a specific data in producing new designs for typical buildings plans, such as schools, without the use of ready software in the generation process.The research sought to obtain a number of alternative plans according to the user inputs. It hypothesized that the variation in the design inputs contributes effectively to the plurality of the generated design options.  The findings verified that the method was feasible regarding the problem with specific data under consideration. In addition, it showed the efficiency of the generative algorithm approach in producing various designs that meet the different inputs of the user.